2020
DOI: 10.1111/fcp.12551
|View full text |Cite
|
Sign up to set email alerts
|

Urolithin C increases glucose‐induced ERK activation which contributes to insulin secretion

Abstract: Polyphenols exert pharmacological actions through protein‐mediated mechanisms and by modulating intracellular signalling pathways. We recently showed that a gut‐microbial metabolite of ellagic acid named urolithin C is a glucose‐dependent activator of insulin secretion acting by facilitating L‐type Ca2+ channel opening and Ca2+ influx into pancreatic β‐cells. However, it is still unknown whether urolithin C regulates key intracellular signalling proteins in β‐cells. Here, we report that urolithin C enhanced gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…This effect was induced by regulating cell surface proteins and intracellular signaling pathways including facilitation in L‐type Ca 2+ channel opening and the Ca 2+ influx into INS‐1 cells (Bayle et al, 2019). In 2020, Toubal et al (2020) demonstrated that UroC activated ERK1/2 by phosphorylation in INS‐1 b‐cells. Furthermore, modulation in kinases signaling may be responsible for numerous biological processes.…”
Section: Biological Effects Of Urocmentioning
confidence: 99%
“…This effect was induced by regulating cell surface proteins and intracellular signaling pathways including facilitation in L‐type Ca 2+ channel opening and the Ca 2+ influx into INS‐1 cells (Bayle et al, 2019). In 2020, Toubal et al (2020) demonstrated that UroC activated ERK1/2 by phosphorylation in INS‐1 b‐cells. Furthermore, modulation in kinases signaling may be responsible for numerous biological processes.…”
Section: Biological Effects Of Urocmentioning
confidence: 99%
“…Bayle and colleagues identified UC as a glucose-dependent activator of insulin secretion through upregulation of calcium flux into pancreatic β-cells [ 17 ]. A further study demonstrated that UC enhanced insulin secretion of β-cells via enhancing glucose-induced activation of the ERK signaling, a key intracellular signaling [ 32 ]. These two studies suggest the potential effects of UC on restraining T1D progression via increasing insulin secretion of β-cells but do not provide any direct in vivo evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Bayle and co-workers studied the effect of polyphenols on pancreatic β-cell functions and pointed out that urolithin C is a glucose-dependent activator of insulin secretion through the activation of L-type Ca 2+ channels. , Consequently, the pharmacological activity of urolithin C could be beneficial in the treatment of type 2 diabetes . Further studies demonstrate that urolithin C also affects the triggering of intracellular signaling proteins influencing the β-cell function, especially the insulin secretion . Urolithin A has also a valuable effect in the glucose metabolism improving insulin sensitivity via regulation of mitochondrial activities and inflammation …”
Section: Human and Microbiota Metabolism: Molecule–microbiota–host Cr...mentioning
confidence: 99%
“…57 Further studies demonstrate that urolithin C also affects the triggering of intracellular signaling proteins influencing the β-cell function, especially the insulin secretion. 59 Urolithin A has also a valuable effect in the glucose metabolism improving insulin sensitivity via regulation of mitochondrial activities and inflammation. 60 Several papers have been recently reported about the antitumoral effect of urolithins.…”
Section: ■ Introductionmentioning
confidence: 99%